Biopolitics and Historic Justice Coming to Terms with the Injuries of Normality (Edition 1) - Braun, Kathrin (transcript Verlag, 2021)
Human rights violations linked to norms of health, fitness, and social usefulness have long been overlooked by Historic Justice Studies. Kathrin Braun introduces the concept of »injuries of normality« to capture the specifics of this type of human rights violation and the respective struggles for historic justice. She examines the processes of Vergangenheitsbewältigung in the context of coercive sterilization, institutional killings, as well as the persecution of homosexual men and of »asocials« under Nazi rule. She argues that an analytic perspective on political temporality allows us to better understand the formation of these biopolitical human rights violations and their exclusion from memory and historic justice.